ANALISIS DAN DAMPAK EKONOMI DIGITAL DI INDONESIA - Yoseph Erbito; Solikhin Solikhin; Tri Purwani (Institut Teknologi dan Bisnis Kristen Bukit Pengharapan, 2025)
The digital economy refers to all economic activities that utilize digital technology and the internet as their main platform. In recent years, the digital economy has experienced rapid growth, having a significant impact on economic growth, innovation, and changes in consumer behavior. This article aims to examine various aspects of the digital economy, including its impact on economic sectors, the challenges it faces, and the policies needed to support its growth. In Indonesia, the digital economy is growing rapidly and is expected to continue to increase in line with the increasing penetration of the internet and smartphone usage. However, challenges such as cybersecurity, data privacy, and uneven infrastructure need to be addressed. The government and the private sector must work together to create an environment that supports the sustainable growth of the digital economy, so that Indonesia can take advantage of its enormous potential in the global digital economy.